2017
DOI: 10.1016/j.jnutbio.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Apple and blackcurrant polyphenol-rich drinks decrease postprandial glucose, insulin and incretin response to a high-carbohydrate meal in healthy men and women

Abstract: Postprandial glycemic responses to meals are inhibited by polyphenol-rich plant foods. Combinations of polyphenols may be particularly effective through complementary mechanisms. A randomized, controlled, double-blinded cross-over trial was conducted in healthy volunteers to test the hypothesis that apple and blackcurrant polyphenol-rich drinks would reduce postprandial blood glucose concentrations. Secondary outcomes included insulin and glucose-dependent insulinotropic polypeptide (GIP) secretion. Twenty men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 44 publications
11
87
1
1
Order By: Relevance
“…In contrast, the polyphenol-rich and reference bars used in the present study contained no soluble fibre and did not differ in viscosity. Indeed similar to the present study, Castro-Acosta (8,9) removed fibre as a potential confounding variable (i.e. by testing apple and blackcurrant extracts) and observed that the fruit extract modulated the glycaemic response to fruit juice and white bread with apricot jam.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, the polyphenol-rich and reference bars used in the present study contained no soluble fibre and did not differ in viscosity. Indeed similar to the present study, Castro-Acosta (8,9) removed fibre as a potential confounding variable (i.e. by testing apple and blackcurrant extracts) and observed that the fruit extract modulated the glycaemic response to fruit juice and white bread with apricot jam.…”
Section: Discussionsupporting
confidence: 85%
“…In support, some studies have shown that whole berries, berry extracts, apple extract or juice and a mixture of polyphenol and fibre-rich foods (e.g. green tea, apple peel and freeze-dried berry powders) modulate the glycaemic response following consumption of sugar water or starch-based food items (8)(9)(10)(11)(12)(13)(14) . For example, Torronen et al (13,14) demonstrated that consuming polyphenol-rich berry nectars or berry purees with a high-carbohydrate food favourably modulated postprandial glycaemia in healthy adults by slowing glucose absorption and enhancing insulin and glucagon-like peptide-1 (GLP-1) secretion.…”
mentioning
confidence: 95%
“…Similar trend was also observed in normal rats. Similar fi ndings were reported for apple and blackcurrant polyphenol-rich drinks (CASTRO-ACOSTA et al, 2017). Dietary supplementation with Lactobacillus mali strain also effectively maintained blood glucose level in high-fat diet-induced obese mice (LIN et al, 2016).…”
Section: Postprandial Blood Glucose Level Effectssupporting
confidence: 81%
“…More recently, Castro-Acosta et al [108] published the results of a randomized, controlled, double-blinded, crossover trial conducted in healthy volunteers to investigate if enriched polyphenol drinks based on apple [Malus sylvestris (L.) Mill., Rosaceae] and blackcurrant (Ribes nigrum L.) could affect postprandial blood glucose concentrations. They analyzed different parameters, including GIP secretion, in 20 men (age average: 26 years old) and 5 postmenopausal women (age average: 57 years old) who consumed two polyphenol-rich drinks containing fruit extracts or placebo.…”
Section: Clinical Trialsmentioning
confidence: 99%